Extractivism and environmental legislation in Costa Rica. Is the natural heritage preserved? - Blanco Obando, Edgar Eduardo (2021)
This article evaluates through longitudinal analysis of primary and secondary sources, the environmental impact of extractive activities in Costa Rica in relation to environmental legislation, to determine if the country's natural heritage is preserved. Thus, the conclusion is that, extractive activities operate with not legal regulation, what it is against environmental conservation and preservation of natural heritage.